Imido-P(V) trianion supported enantiopure neutral tetrahedral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Paithankar, Harshad; Chugh, Jeetender; Steiner, Alexander; Boomishankar, Ramamoorthy (Chemical Communications, 2018)
Charge-neutral chiral hosts are attractive due to their ability to recognize a wide range of guest functionalities and support enantio-selective processes. However, reports on such charge-neutral cages are very scarce in the literature. Here, we report an enantiomeric pair of tetrahedral Pd(II) cages built from chiral tris(imido) phosphate trianions and oxalate linkers, which exhibit enantioselective separation capabilities for epichlorohydrin, beta-butyrolactone, and 3-methyl- and 3-ethyl cyclopentanone.